2016
DOI: 10.1186/s12974-016-0611-x
|View full text |Cite
|
Sign up to set email alerts
|

Complement is activated in progressive multiple sclerosis cortical grey matter lesions

Abstract: BackgroundThe symptoms of multiple sclerosis (MS) are caused by damage to myelin and nerve cells in the brain and spinal cord. Inflammation is tightly linked with neurodegeneration, and it is the accumulation of neurodegeneration that underlies increasing neurological disability in progressive MS. Determining pathological mechanisms at play in MS grey matter is therefore a key to our understanding of disease progression.MethodsWe analysed complement expression and activation by immunocytochemistry and in situ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
103
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 108 publications
(121 citation statements)
references
References 42 publications
11
103
0
1
Order By: Relevance
“…We have previously shown that complement is activated in progressive MS GM neurons and complement activation correlated with severity of GM pathology, whereas others have shown that complement C1q and C3b expression is associated with degenerating synapses in the progressive MS hippocampus . We performed ISH for complement transcripts that encode the recognition fragment C1q and the central complement component C3.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously shown that complement is activated in progressive MS GM neurons and complement activation correlated with severity of GM pathology, whereas others have shown that complement C1q and C3b expression is associated with degenerating synapses in the progressive MS hippocampus . We performed ISH for complement transcripts that encode the recognition fragment C1q and the central complement component C3.…”
Section: Resultsmentioning
confidence: 99%
“…Probe design consisted of antisense C1QA (NM_015991) FAM‐TggTccTugAugTuuCcuG and sense FAM‐CagGaaAcaTcaAggAccA; antisense C3 (NM_000064) FAM‐TagAaaGugAugGagAcuA and sense FAM‐AgaAauGauUggUggAuuA; antisense CXCL13 (NM_006419) FAM‐AuuGacTugTucTucTucC and sense FAM‐GgaAgaAgaAcaAguCaaT (where capitals indicate LNA and lower case 2′‐O‐Methyl RNA in all instances; Eurogentec, Southampton, UK). ISH was performed as previously described, and hybridization and wash conditions were optimized so that all sense probes yielded essentially no signal. Appropriate sense probes and no probe controls were included in every experimental run.…”
Section: Methodsmentioning
confidence: 99%
“…Fibrin(ogen), as a potent activator of microglial/ macrophage inflammation, might be a novel therapeutic target that could limit ongoing maladaptive innate immune responses in advanced progressive MS. 6 Activation of cortical microglia/macrophages by fibrin(ogen) might be an early interaction setting the stage for diffuse neuroaxonal loss characteristic of progressive disease through several potential mechanisms, including the generation of reactive oxygen species, 32 glutamate excitotoxicity, 33 and deposition of complement as recently described. 34 In summary, we introduce cortical fibrin(ogen) deposition as a novel component of cortical pathology in progressive MS. We show that fibrin(ogen) is extensively deposited in the progressive MS motor cortex where regulation of fibrinolysis appears perturbed. The inverse relationship between neuronal density and fibrin(ogen) deposition in the MS motor cortex highlights the functional relevance of this protein in disease progression.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, this classical complement cascade-mediated phagocytic signaling has now been identified to be aberrantly upregulated in mouse models of Alzheimer’s disease, frontotemporal dementia, and West Nile Virus infection, leading to synapse loss (Hong et al, 2016, Vasek et al, 2016, Lui et al, 2016). In MS patients, complement proteins are elevated systemically and in the CNS (Aeinehband et al, 2015, Ingram et al, 2012, Ingram et al, 2009, Watkins et al, 2016), and recent work has suggested that C1q and C3 colocalize with synaptic proteins in postmortem MS brains (Michailidou et al, 2015). However, it remains elusive if complement and/or microglia are necessary for synaptic changes in MS.…”
Section: Introductionmentioning
confidence: 99%